Tenofovir disoproxil fumarate/emtricitabine is associated with a higher risk of hypocalcemia compared to abacavir/lamivudine – results from a German cohort study. (April 2019) - Noe, S; Heldwein, S; Jaeger, H; Page, M; Wolf, E
Hyperparathyroidism has been described in people living with HIV undergoing tenofovir disoproxil fumarate (TDF)-containing antiretroviral therapy (ART), but differences in calcium levels have never been investigated in detail. We aimed to compare the prevalence of hypocalcemia between patients with and without TDF-containing ART. The patients and methods were a retrospective cohort study in HIV-infected adult patients receiving dolutegravir and either abacavir (ABC)/lamivudine (3TC) or TDF/emtricitabine in a single center in Munich, Germany. Of 172 patients, 126 (73.3%) were male and the median age was 48.5 years (interquartile range 42–54). Average calcium levels were 2.24 (2.21–2.29) mmol/l and 2.21 (2.16–2.26) mmol/l (P < 0.001) with a prevalence of at least one episode of total calcium <2.12 mmol/l of 16.2 and 34.4% in the groups treated with ABC/3TC and TDF/emtricitabine, respectively (P = 0.006). TDF use was independently associated with the occurrence of albumin-corrected calcium levels of <2.12 mmol/l (odds ratio: 6.7 [1.3–35.6]; P = 0.025). Hypocalcemia seems to occur more often in TDF-treated patients. Further research into hypocalcemia with TDF and potential cardiovascular effects may be of benefit based on these findings.